Moral Universalism at a Time of Political Regression: A Conversation with Jürgen Habermas about the Present and His Life's Work - Claudia Czingon; Aletta Diefenbach; Victor Kempf (Theory, Culture & Society, 2020)
In the present interview, Jürgen Habermas answers questions about his wide-ranging work in philosophy and social theory, as well as concerning current social and political developments to whose understanding he has made important theoretical contributions. Among the aspects of his work addressed are his conception of communicative rationality as a countervailing force to the colonization of the lifeworld by capitalism and his understanding of philosophy after Hegel as postmetaphysical thinking, for which he has recently provided a comprehensive historical grounding. The scope and relevance of his ideas can be seen from his reflections on current issues, ranging from the prospects of translational democracy at a time of resurgent nationalism and populism, to political developments in Germany since reunification, to the role of religion in the public sphere and the impact of the new social media on democratic discourse.
Keywords: 300; capitalism; communicative reason; EU; postmetaphysical thinking; public sphere; postsecularism; transnational democracy